Explosive pulsed power - Altgilbers, Larry L. (London : Imperial College Press, 2011)
'Explosive pulsed power generators are devices that either convert the chemical energy stored in explosives into electrical energy or use the shock waves generated by explosives to release energy stored in ferroelectric and ferromagnetic materials. The objective of this book is to acquaint the reader with the principles of operation of explosive generators and to provide details on how to design, build, and test three types of generators: flux compression, ferroelectric and ferromagnetic generators, which are the most developed and the most near term for practical applications. Containing a considerable amount of new experimental data that has been collected by the authors, this is the first book that treats all three types of explosive pulsed power generators. In addition, there is a brief introduction to a fourth type ix explosive generator called a moving magnet generator. As practical applications for these generators evolve, students, scientists, and engineers will have access to the results of a considerable body of experience gained by almost 10 years of intense research and development by the authors.'--Publisher description.
Fundamentals of electromagnetic theory and electric circuits -- Fundamentals of shock waves and high explosives -- Measurement techniques -- Flux compression generators -- Helical flux compression generators -- Magnetic materials and circuits -- Ferromagnetic generators -- Ferroelectric materials and their properties -- Phase transformations in ferroelectric crystals -- Ferroelectric shock depolarisation studies -- Ferroelectric generators -- Moving magnet generators -- Case studies.
Includes bibliographical references and index.
Keywords: Pulsed power systems; Pulsed power systems -- Design and construction